Is life without parole an effective way to reduce violent crime? An empirical assessment - Kleinstuber, Ross; Coldsmith, Jeremiah (Criminology & Public Policy, 2020)
Research Summary By taking advantage of data published by the Sentencing Project to analyze whether states that use life without parole (LWOP) more often experience lower violent crime rates or greater reductions in violent crime, this study is the first to empirically assess the crime-reducing potential of LWOP sentences. The results suggest that LWOP might produce a small absolute reduction in violent crime but that it is no more effective than life with parole. Policy Implications Despite reductions in the use of the death penalty, LWOP has expanded dramatically—and at a much faster rate—over the last quarter century. This expansion has come at great financial and human costs and has not been distributed equally throughout the population. As such, the public policy debate over the use of LWOP is likely to intensify. Yet, to date, there have been no empirical assessments of LWOP's efficacy to inform this debate. This study begins to fill this gap in our knowledge, and the results, if replicated, suggest that the use of LWOP should be either scaled back or eliminated.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/1745-9133.12496